WAKTU PENANGKAPAN KEPITING BAKAU (Scylla serrata) DI PERAIRAN LONTAR KABUPATEN SERANG BANTEN - Ririn Irnawati; Adi Susanto; Siti Lulu Ayu Maesaroh (Jurnal Perikanan dan Kelautan, 2014)
Lontar is one area of the mud crab fishing in Serang Regency. The collapsible traps are commonly used by Lontar’s fisherman to catch mud crab. This study aimed to describe the collapsible trap fishing unit, operation method and analyze the effect of different catching time in Lontar. The experimental fishing was conducted for 30 days. The result showed that the collapsible traps have size LxWxH= 42x29x17 cm with a frame diameter of 0,35 cm, using polyethylene multifilament with a mesh opening of 1 cm as a covered and operated by one fisherman. The main parts of the collapsible trap are body, funnel, frame, bait place and buoys. Operation methods divided into setting, soaking and hauling. The main catches consist of mud crab (Scylla serrata). By catch on the collapsible trap including swimming crab (Portunus pelagicus) and spiral babylonia (Babylonia spirata). Result of t-test showed that fishing time has significant influenced to total weight and total number of catch. It means total weight and number of catch at the night higher than the day.Keyword: fishing, mud crab, time, trap